Cerebral herniation syndromes and intracranial hypertension - Koenig, Matthew, 1975- (Updates in neurocritical care., 2016)
Bringing together internationally-renowned neurocritical care experts from a variety of neurology, critical care, surgery, and neurosurgery disciplines, Cerebral Herniation Syndromes and Intracranial Hypertension takes a comprehensive look at the complex relationship between intracranial pressure and cerebral herniation syndromes. Drawing from expertise gained working in high-volume medical centers, the book's contributors demonstrate the best practices for offering individualized care to brain injury patients, based on their specific conditions and manifest symptoms.